PEMANFAATAN SUMBER BELAJAR DALAM PEMBELAJARAN IPS OLEH GURU DI SMPN BANDA ACEH - Mauliana Wahyudi; Ruaida Ruaida; Nana Suraiya (Jurnal Pendidikan Geosfer, 2016)
Based on this the researchers conducted this study aimed to determine (1) the learning resources used by teachers in SMPN Banda Aceh (2) constraints experienced by teachers in the use of learning resources in the learning of IPS (3) the efforts of teachers to seek solutions in the utilization of resources learn. This study used a qualitative approach with descriptive research. Subjects in this study was a social studies teacher at SMPN Banda Aceh consisting of 10 teachers. Data collection techniques in this study in the form of documentation and interviews. Data analysis technique used is data reduction, data presentation in the form of descriptive to draw conclusions. The results showed that 8 out of 10 social studies teachers who were respondents in this study have made use of learning resources IPS diverse and followed by media use social studies, but there are 2 of the 10 respondents who have never used the environment outside the school as a source of learning IPS as museum , offices or tourist attractions, the obstacles encountered in the use of learning resources outside the school environment such as cost, distance and time as well as the limitations of school facilities, the efforts of many teachers assign students to search for information through the internet as a homework assignment.